MEMAHAMI KONSEP KESELAMATAN DI LUAR KRISTEN BERDASARKAN 1 TIMOTIUS 2:5-6 - Lawolo, Yarnia; Lawolo, Andianus; Lawolo, Semita; Koswanto, Alvin (CARAKA: Jurnal Teologi Biblika dan Praktika, 2024)
One of the issues in Christianity that has become a problem and debate among Christian theologians to this day is the rejection of salvation outside of Christianity. They claim salvation can only be obtained through Christianity. Non-Christians do not get salvation to enter heaven, they automatically enter hellfire. The purpose of this study is to understand the concept of salvation outside Christianity correctly based on the analysis of 1 Timothy 2:5-6. The researcher used a qualitative method with a literature study approach through various relevant sources, such as the Bible, books, journal articles and credible documents. The results of this study found that salvation is not only obtained by believers (Christians), while non-Christians go to hell. Rather, non-Christians also obtain salvation for those who live based on good morals and ethics and live according to the law. They are welcomed into heaven as members of society. In contrast to Christians who are centered on Jesus Christ and wear the life of Jesus on this earth, later they will reign with God in the new heavens and new earth. Salvation is not determined by one's religion, but faith expressed through concrete actions every day. 1 Timothy 2:5-6, the salvation that Jesus worked out 2000 years ago through the redemption of the sins of all mankind is universal salvation or all mankind.